Improvement of Jumping Combinations to Football Games - Ahmad Atiq; Wiwik Yunitaningrum; Novi Yanti; Rubiyatno Rubiyatno; Rahmat Putra Perdana; Muhammad Ali; Fitrya Mustika Andriani (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study aims to determine the increase in the combination of running and jumping in soccer games. Court tennis game. This study uses a CAR approach (Classroom Action Research), the research carried out intends to find information about the implementation of learning variations delivered by classroom action research. The population is 26 students of Class V at the State Elementary School 13 Batu Ampar. Following this type of research, namely classroom action research, this research has staged in the form of cycles. The design of each cycle consists of four stages, namely planning, implementation, observation, and reflection. From the results of research cycle 1, 20 students have completed with a percentage of 74% divided into 2 classifications ranging from 75-79 and 80-89 and 6 students who have not completed with a percentage of 24%. Then from cycle 2, there were no students who had not achieved the completeness score because they scored below 75 and 35 other students were declared complete after getting a score above 75. It means that learning the combination of running and jumping can improve learning outcomes on football material.